The rotation angle distribution underlying magnetic field fluctuations in the 1/f range of solar wind turbulent spectra - Matteini,L; Stansby,D; Horbury,TS; Chen,CHK (Il Nuovo Cimento C – Colloquia and Communications in Physics, 2019)
We discuss properties of large amplitude magnetic field fluctuationsduring fast Alfv eenic solar wind streams, focussing on the statistics of the rotationangle between consecutive magnetic field vector measurements for different scalesin the plasma. Since in the fast solar wind fluctuations preserve the modulus ofthe magnetic field to a good approximation, the tip of the magnetic field vector isobserved to move on a sphere of approximately constant radius|B|.Wethencom-pare statistics of solar wind measurements with that of a simple model of a randomwalk bounded on a spherical surface. The analogy consists in the fact that in bothsystems the geometrical constraint imposes a limiting amplitude at large separa-tions and thus introduces a break scale in the power spectrum of the fluctuations,leading to a shallower slope for scales where the fluctuations amplitude becomesscale-independent. However, while in the case of the random walk the saturationof the fluctuations occurs when the pattern becomes uniform on the sphere (flatdistribution of the cosine of the rotation angle), transitioning then to a white noiseregime, in the solar wind magnetic field fluctuations saturate in amplitude maintain-ing a preferential direction. We suggest that this behaviour is due to the presence ofthe background interplanetary magnetic field, which keeps some long-range memoryin the system also when the fluctuations becomes independent of the scale. Thislong-range correlation is a necessary ingredient in order to produce the 1/fspectrumobserved at large scales in the solar wind.